The relationship between type d personality and impulsivity in medicine, dentistry, and nursing students - YILDIZ, MESUT (My University, 2023)
Amaç: D tipi kişilik negatif afektivite (NA) ve sosyal inhibisyonun (SI) belirgin olduğu bir kişilik tipi olarak tanımlanmaktadır. D tipi kişilik psikiyatrik semptomlarla ilişkilidir. Bu çalışmanın amacı klinik olmayan bir popülasyonda Tip D kişilik ile dürtüsellik arasındaki ilişkinin araştırılmasıdır. Gereç ve Yöntem: Çalışmaya toplamda sağlık alanında eğitim gören 462 üniversite öğrencisi dahil edilmiştir. Katılımcılara Beck Anksiyete Ölçeği (BAI), Beck Depresyon Ölçeği (BDI), Barratt Dürtüsellik Ölçeği-11 (BIS-11) ve D Tipi Kişilik Ölçeği (DS-14) ile değerlendirilmiştir. Bulgular: D tipi kişiliğin sıklığı % 39.6 idi. D tipi kişiliği olanlarda olmayanlarda göre BAI, BDI ve BIS ölçek skorları daha yüksek bulunmuştur. Korelasyon analizinde D tipi kişiliğin depresyon ve anksiyetenin şiddetiyle pozitif olarak korele olduğu gösterilmiştir. BIS ile ölçülen dürtüsellik skorlarının D tipi kişilik, depresyon ve anksiyete skorları ile pozitif yönde korele oldukları görülmüştür. Regresyon analizinde ise dürtüselliğin erkek cinsiyet ev depresyon skorları ile predikte edildiği gösterilmiştir. Sonuç: D tipi kişiliğik depresyon ve anksiyete şiddetiyle koreledir. Depresyon puanları ve erkek cinsiyet dürtüselliği yordamaktadır

Aim: Type D personality is defined as a type in which negative affectivity (NA) and social inhibition (SI) are prominent. Type D personality is associated with psychiatric symptoms. The present study aims to investigate the relationship between Type D personality and impulsivity in a non-clinical population. Material and Method: In total, 462 undergraduate health Professional students were recruited for the study. Subjects were evaluated using Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI), Barratt Impulsivity Scale-11 (BIS-11), and Type D Personality Scale (DS-14). Results: The frequency of type D personality was 39.6%. The BAI, BDI, and BSI scores were higher in participants with Type D personality compared to the group without Type D personality. Correlation analysis demonstrated that Type D personality was positively correlated with the severity of depression and anxiety. Impulsivity scores measured by the BSI was posivitely correlated with Type D personality, depression, and anxiety scores. Regression analysis demonstrated that impulsivity was predicted by male sex and depression scores. Conclusion: Type D personality was correlated with the severity of depression and anxiety. Depression scores and male sex predicted impulsivity.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)